Climate control on stacked paleosols in the Pleistocene of the Po Basin (northern Italy). (13th April 2020) - Bruno, Luigi; Marchi, Michela; Bertolini, Ilaria; Gottardi, Guido; Amorosi, Alessandro
ABSTRACT: Paleosols are recurrent features in alluvial successions and provide information about past sedimentary dynamics and climate change. Through sedimentological analysis on six sediment cores, the mud‐dominated succession beneath the medieval 'Two Towers' of Bologna was investigated down to 100 m depth. A succession of weakly developed paleosols (Inceptisols) was identified. Four paleosols (P1, P2, P3 and PH) were radiocarbon‐dated to 40–10 cal ka bp . Organic matter and CaCO3 determinations indicate low groundwater levels during soil development, which spanned periods < 5 ka. The development and burial of soils, which occurred synchronously in the Bologna region and in other sectors of the Po Plain, are interpreted to reflect climatic and eustatic variations. Climatic oscillations, at the scale of the Bond cycles, controlled soil development and burial during Marine Isotope Stage (MIS) 3 (P1 and P2). Rapid sea‐level oscillations probably induced soil development at the MIS 3/2 transition (P3) and favored burial of PH after 10 ka bp . Weakly developed paleosols in alluvial successions can provide clues to millennial‐scale climatic and environmental variations. In particular, the paleosol‐bearing succession of the Po Plain represents an unprecedent record of environmental changes across the Late Pleistocene (MIS 3 and 2) in the Mediterranean region.